Ultrasound Guided Continuous Quadratus Lumborum Block as a Perioperative Analgesic Technique for Pyeloplasty in a Paediatric Patient : A Case Report - Yadav, Rupesh Kumar; Dhungel, Bidur; Thapa, Bijay (Birat Journal of Health Sciences, 2020)
With the use of ultrasound, peripheral nerve blocks can be more precise and deposition of local anesthetics under direct vision reduces drug volume and minimizes untoward toxicity. Its extensive use in peri-operative period add a safety measures to reduce procedural complications. Pain in children's are often under recognized and under treated which can lead to emotional, psychological trauma for rest of their life. Peripheral nerve blocks have the advantage of greater overall safety and efficacy for lower abdominal surgeries. An abdominal truncal block technique known as Quadratus Lumborum block has emerged recently with a goal of anesthetizing the thoracolumbar nerves for somatic as well as visceral analgesia of both lower and upper abdomen. A sound knowledge of sensory supply to the genitourinary system is important for the success of regional anesthesia. We report a case of four years old child who was diagnosed as left sided pelvic ureteric junction obstruction and was planned for pyeloplasty where continuous quadratus lumborum block was used as a mode of post operative analgesia which showed a promising result. Antibiotic resistance and lack of newer effective antibiotic against multidrug resistant bacteria like Acinetobacter baumannii is a common problem in intensive care unit. Trimethoprim -Sulfamethoxazole may help in combating this problem.